ArtMatters : Netherlands Technical Studies in Art (vanaf 2008: ondertitel varieert: International Journal for Technical Art History). (Zwolle London : Waanders Archetype Publications, 2002)
Technical Art History examines the act of art-making in all its facets, from all forms, times, and places. Its approach is interdisciplinary and combines the humanities and social sciences, as well as heritage science and conservation research to understand methods and materials of artistic practice. From initial idea to finished object, from making process to survival over time, the object’s biography takes central stage, set against ever-evolving cultural, political, economic, and social environments. At the core of Technical Art History as a discipline are technological texts and archival documents describing methods and materials; reconstructions as research tools; research into workshop practices; as well as exchanges of knowledge and materials between disciplines, from medieval times to present art production. Innovative digital methods are increasingly playing a crucial role within technical art history. Other focus points for current research include female artists and makers; the global exchange of techniques; the history of trade in artists’ materials, artistic and artisanal skills; the complexity of contemporary art practice; as well as the preservation of intangible cultural heritage such as the preservation of disappearing knowledge of specific crafts and artistic techniques.(www.amjournal.org)
Online: https://www.amjournal.org/past-issues
Engels
Jaarboek